2021
DOI: 10.1021/acscatal.1c05208
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Bromination Enables Formal Cross-Electrophile Coupling of Alcohols with Aryl and Alkenyl Halides

Abstract: Although alcohols are one of the largest pools of alkyl substrates, approaches to utilize them in cross-coupling and crosselectrophile coupling are limited. We report the use of 1°and 2°alcohols in cross-electrophile coupling with aryl and vinyl halides to form C(sp 3 )− C(sp 2 ) bonds in a one-pot strategy utilizing a very fast (<1 min) bromination. The reaction's simple benchtop setup and broad scope (42 examples, 56% ± 15% average yield) facilitates use at all scales. The potential in parallel synthesis app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 52 publications
0
48
0
Order By: Relevance
“…We note that a broader ligand screen that includes low-performing ligands from Table 1 could be helpful. [32] Whereas N-cyano carboxamidine ligands like L7 have proven increasingly useful in cross-electrophile coupling, [23,24 ] no structural characterization of their nickel complexes has been reported. We were able to synthesize Ni(L7)(o-tol) by reaction of the free ligand with trans-(Ph 3 P) 2 Ni(o-tol)Br.…”
Section: Resultsmentioning
confidence: 99%
“…We note that a broader ligand screen that includes low-performing ligands from Table 1 could be helpful. [32] Whereas N-cyano carboxamidine ligands like L7 have proven increasingly useful in cross-electrophile coupling, [23,24 ] no structural characterization of their nickel complexes has been reported. We were able to synthesize Ni(L7)(o-tol) by reaction of the free ligand with trans-(Ph 3 P) 2 Ni(o-tol)Br.…”
Section: Resultsmentioning
confidence: 99%
“…One method involves the in situ conversion of the hydroxyl motif into the corresponding iodide or bromide, which subsequently reacts via metal‐catalysed coupling in a one‐pot cascade strategy. Inspired by this concept, Gong [47] and Weix [48] concurrently reported Ni‐catalysed methodologies for the formal cross‐coupling of alcohols with aryl halides (Gong) and aryl/alkenyl halides (Weix) (Scheme 29). The former employed 2‐chloro‐3‐ethylbenzo[ d ]‐oxazol‐3‐ium salts (CEBO) 61 as in situ halogenating reagents, while the latter utilised Hendrickson's POP reagent 62 [49] to achieve this goal.…”
Section: Deoxygenative C−c Bond Formationmentioning
confidence: 99%
“…Scheme 34 Cross-electrophile coupling of alcohols with aryl halides via hologenation by CEBO/TBAX Recently, Weix reported another method of in situ conversion of alcohols into alkyl bromides used in tandem crosselectrophile coupling with aryl and vinyl halides (Scheme 35). 72 The fast, homogeneous bromination system, POP/TBAB in MeCN and the employing of a new ligand, alone or with other ligand are key to provide high yields of products. They found that the mothed was effective for the coupling of a wide range of 1° and 2° alcohols with aryl, heteroaryl and vinyl bromides.…”
Section: Scheme 33 Photo-induced Carbene-mediated Deoxygenative Aryla...mentioning
confidence: 99%